Improving Quality and Lowering Cost Through Community Care Teams. Issue 4 (July 2018) - Fleming, Hannah-Kaye
Abstract : EXECUTIVE SUMMARY: The U.S. healthcare industry has seen a sharpened focus on delivering value-based care. To accomplish this, providers have turned their attention toward high-risk patients who are in frequent contact with the healthcare system. Specific attention has been given to Medicaid patients, who make up a majority of the high-risk population. Providers are implementing new approaches and strategies to improve the quality of healthcare and lower the cost for high-risk Medicaid patients. This essay highlights how the implementation of community care teams (CCTs) can improve quality and lower costs for these patients. Through discussion of the success at Community Care North Carolina, other states can understand the impact CCTs have on high-risk Medicaid patients by delivering value-based care, improving quality, and lowering costs.